Recombinant interleukin 4/BSF-1 promotes growth and differentiation of intrathymic T cell precursors from fetal mice in vitro. - Palacios, R (1987)
Recombinant mouse interleukin 4/BSF-1 (rIL4/BSF-1) together with phorbol myristate acetate (PMA) promotes growth of one out of approximately four intrathymic T cell precursors from fetal mice (14-15 days gestation). This response is not inhibited by even high concentrations of monoclonal antibody against the receptor for interleukin 2. Fetal thymocytes activated by rIL4/BSF-1 plus PMA give rise to cytolytic T cells after 7-21 days of culture. All the proliferating cells are Thy1+, some of them express Lyt2 but none has detectable L3T4 T cell differentiation antigens nor T cell antigen receptor (F23.1) on the cell membrane as assessed by immunofluorescence staining and flow fluorocytometry analysis. It is concluded that rIL4/BSF-1 exerts both growth and differentiation activities on normal intrathymic T cell precursors. The results provide evidence for an alternative growth factor to interleukin 2 involved in proliferation of T cell precursors. These findings open new and direct ways of studying cellular and molecular events during the differentiation of normal intrathymic T cell precursors in vitro and extend the spectrum of target cells for IL4/BSF-1.